(untitled) (Nordic Journal of African Studies, 2004)
Many studies have confirmed that code-switched structures have some underlying grammatical and semantic rules that account for their well-formedness and acceptability. The importance of the heads in their structures has, however, not been fully explored. This paper studies the interaction of functional and lexical heads and the scope of each. It confirms that while functional heads legislate on the structure of an expression, lexical heads regulate the meaning of the structure. This is done through their influence over elements within their respective scopes. The Scope Limiting Constraint is proposed to account for the overlap between two heads as they co-operate to ensure grammaticality and acceptability of expressions.